An Overview of Central Nervous System Tumours - Brian Thabile Flepisi; Marissa Balmith (Ital Publication, 2021)
Central nervous system (CNS) tumours refer to tumours that occur in the tissues of the brain and/or spinal cord. These tumours arise as a result of abnormal growth of cells and may begin in different parts of the brain or spinal cord. There are many types of CNS tumours, which are further divided into subtypes. Despite decades of research conducted, CNS tumours remain among the deadliest of all cancers. It is most often challenging to treat these tumours, due to the risks involved, and biological characteristics associated with them. The classification, grading, and characterisation of CNS tumour plays a pivotal role in the management thereof. The current review provides an overview of CNS tumours, classification, grading and treatment, as well as their characterisation with specific focus on gliomas, ependymomas, oligodendrogliomas, meningiomas, medulloblastomas, schwannomas, gangliogliomas, and craniopharyngiomas.   Doi: 10.28991/SciMedJ-2021-0304-8 Full Text: PDF